First Midwestern Exhibition of Belgian Painters. - The Arts Club of Chicago; The Art Gallery, University of Notre Dame; The Toledo Museum of Art, Toledo; Contemporary Arts Center, Cincinnati; The University Gallery, University of Minnesota (Chicago : The Arts Club of Chicago, 1961)
Alechinsky, Pierre ; Bertrand, Gaston ; Boel, Maurice ; Bonnet, Anne ; Delahaut, Jo ; Delvaux, Paul ; Landuyt, Octave ; Maes, Jacques ; Peire, Luc ; Servranckx, Victor ; Slabbinck, Rik ; Van Lint, Louis ; Wolvens, Henri
First Midwestern Exhibition of Belgian Painters, The Arts Club of Chicago, september 28 to October 28, 1961 / The Art Gallery, University of Notre Dame, November 19 to December 17, 1961 / The Toledo Museum of Art, Toledo, January 12 to February 12, 1962 /Contemporary Arts Center, Cincinnati, March 5 to April 2, 1962 / The University Gallery, University of Minnesota, April 16 to May 14, 1962
boek